(3MGTjI Ydi TQM LeY GdLheYs - (3GdTYQGfi Ydj Hf Ydj Hf CMeO GdfLGQ GdTGaYjs ((3eMeO Hf eMeO ehSi s)
(3ChdgG (B:s
(3hHYO ajbhd GdYHO GdabjQ gPg MhGTi Ydi GdTQM GdeTghQ HTQM LeY GdLhGeY s
(3BNQgG (B:s
(3aQZJ ef gPg GMhGTi jhe GdSHJ s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3CUhd Gdabgs